Impacts of Bipolar Impulse Parameters on the PDIV of Random-Wound Inverted-Fed Motor Insulation - Junsheng Chen; Peng Wang (Energies)
The detection of Partial Discharge Inception Voltage (PDIV) is vital for evaluating the insulation performance of random-wound inverter-fed motor stators. However, existing research on the impact of impulse parameters on PDIV patterns and their underlying mechanisms is limited, leading to inadequate guidelines for choosing suitable impulse parameters during PDIV tests of stator insulation under impulsive conditions. This lack of understanding significantly affects the precision of the accuracy of insulation test results for inverter-fed motors. To bridge this gap, this study systematically investigated the influence of key impulse parameters, such as pulse width, dead time, and impulse frequency, on the PDIV test outcomes in enameled wire samples (enameled twisted pairs and pig-tail wires) and random-wound inverter-fed motor stators. A differential bipolar repetitive impulse voltage and a sinusoidal voltage were applied to simulate the pulse-width modulation electrical stress typically experienced by these motors. Results reveal a negative correlation between PDIV test results and pulse width, a positive correlation with dead time, and a weak correlation with impulse frequency. Furthermore, the potential fundamental mechanisms are proposed for the influence of impulse voltage parameters on PDIV characteristics by analyzing the electric field distribution and discharge processes within insulating materials when subjected to impulsive voltages. Based on the experimental conclusion, this study proposes targeted recommendations for revising the current IEC testing standards. These improvements are anticipated to refine stator insulation testing methodologies for inverter-fed motors, ultimately contributing to enhanced insulation reliability in such electric motors.